Identification of Potential Landslide Areas in Nusaniwe Sub-district, Ambon City using Slope Morphology Method - Rakuasa, Heinrich (Universitas Budi Luhur, 2024)
This study aims to identify potential landslide areas in Nusaniwe Sub-district using the Slope Morphology Method (SMORPH) based on slope and slope shape analysis. The results show that the complex geological and topographical conditions in the area increase the risk of landslides, with areas of high slope and steep slope shapes tending to be landslide hotspots. Interdisciplinary collaboration, community education, and the development of effective mitigation strategies are key in reducing the risk of landslides in Nusaniwe Sub-district and similar areas.